2018 IEEE Frontiers in Education Conference (FIE) 2018
DOI: 10.1109/fie.2018.8658805
|View full text |Cite
|
Sign up to set email alerts
|

Learning and academic success in engineering courses: Comparing 1st year students according to gender

Abstract: This work in-progress research to practice paper analyzes the learning achievements of first-year engineering students, in order to observe if there are eventual gender differences. Studies suggest that women have higher enrollment rates and achievements in Higher Education. Women also dedicate more time studying and are more committed attaining their degree than men. Although the percentage of female students' application in Science, Technology, Engineering and Mathematics (STEM) courses increased in the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Students are always the focus of university productivity assessments, and their average grade is usually used as a productivity metric. For example, Vasconcelos and Almeida (2019) assessed the teaching-learning process and academic success in engineering courses, comparing first-year students according to gender and students’ average grades. The authors found that female students have a better organization of their time and study activities, are also more thoughtful and self-regulated learners and have a higher rate of successful curricular units and higher average grades.…”
Section: Theoretical Background Of the Used Methods To Quantify Stude...mentioning
confidence: 99%
“…Students are always the focus of university productivity assessments, and their average grade is usually used as a productivity metric. For example, Vasconcelos and Almeida (2019) assessed the teaching-learning process and academic success in engineering courses, comparing first-year students according to gender and students’ average grades. The authors found that female students have a better organization of their time and study activities, are also more thoughtful and self-regulated learners and have a higher rate of successful curricular units and higher average grades.…”
Section: Theoretical Background Of the Used Methods To Quantify Stude...mentioning
confidence: 99%